THE EFFECT OF ANTICIPATION GUIDING ON STUDENTS LEARNING READINESS IN THE THIRD-GRADE STUDENTS OF ELEMENTARY SCHOOL of SDN SIDOMORO 1, GRESIK - Hidayah, Nur (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2012)
Background The lack of home learning readiness highly influences the learning process. The preventive way by self-home learning may bring positive effects, namely they will be able to understand the teacher’s explanation or tutorial and do what is being instructed in accomplishing assignments or answering questions. Purpose: was to find out the effects of anticipatory guidance on the learning readiness in the third-grade students of elementary school. Method Quasi-experimental with pretest-posttest control group design. The population involved all third-grade students of SDN Sidomoro 1, Kebomas sub-district, Gresik in which 98 respondents were taken as the samples by applying the total sampling technique. The respondents were then classified into two groups: control group and study group, 48 students each. The instrument: observation sheet. The data analysis using descriptive statistic. Result findings the pre-test value of the study group on good learning readiness was shown by 9 students (34.7%). Compared to the post-test value with the same group, 40 students (81.6%) were in good category. On the other hand, among the control group, the pre-test value showed that 20 students (40.8%) also had good learning readiness, whereas the post-test value described that 17 students (36.7%) were also in good learning readiness. Conclusion Based on the result presented above, providing of anticipatory guidance for students of elementary school is very important to increase the readiness of student’s self-learning for the positive effect, learning achievement.